Evaluation of Microbiological Profiles of Diabetic Foot Infections at a Tertiary Hospital - Aydın, Özlem; Çelik, Aykut (Cerrahpaşa Medical Journal, 2022)
Objective: Diabetic foot wounds impair the quality of life of patients and may progress to amputation with the developing infection. In our study, we aimed to evaluate the microbiological profiles and antibiotic susceptibility of diabetic foot infections in this context. Methods: Patients who were hospitalized with the diagnosis of diabetic foot infection and underwent surgical procedures in the orthopedics and traumatology clinic between January 2019 and March 2021 were retrospectively searched from the hospital database. Results: A total of 71 patients were included in the study. Gram-negative bacteria were the most common cause of the infections (66.7%). The highest rate of culture growth was found in Klebsiella pneumoniae as 23.5%, followed by Escherichia coli as 19.8%. The Wagner Grade 4 classification was the most common grade in our patients. The extended-spectrum beta-lactamase rate of the K. pneumoniae isolates was the highest as 57.9%. There was meropenem resistance in 31.6% (n = 6) of the Klebsiella strains, 75% (n = 3) of the Acinetobacter strains, and 33.3% (n = 2) of the Pseudomonas strains. The methicillin resistance rate was 50% in the Staphylococcus aureus strains. Major amputation was performed in 88.7% of the patients, with a post-surgical mortality rate of 9.9%. Conclusion: Diabetic foot ulcers is an important risk factor for extremity loss and can lead to morbidity and mortality. The increasing prevalence of antibiotic resistance in our country is a concern. It is extremely important in the management of infections to detect regional pathogens and susceptibility patterns and initiate empirical treatment by considering potentially influential factors. Cite this article as: Aydın Ö, Çelik A. Evaluation of microbiological profiles of diabetic foot infections at a tertiary hospital. Cerrahpaşa Med J. 2022;46(1):44-49.